2013
DOI: 10.7241/ourd.20132.44
|View full text |Cite
|
Sign up to set email alerts
|

Does pityriasis rosea Koebnerise?

Abstract: The Koebner phenomenon or isomorphic phenomenon is described in dermatology texts as the production of lesions of the original disease, in clinically uninvolved skin, following trauma. The lesions are located at the site of trauma and evidence of a traumatic causation is the linear arrangement of some of the lesions, such as in the case of lichen planus. Other disorders known to exhibit the Koebner phenomenon include psoriasis and vitiligo. A number of other diseases are associated with the Koebner phenomenon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…1 In addition to these known associations, a literature review revealed a few isolated cases of Poland syndrome with various congenital dermatologic findings, including recessive X-linked ichthyosis, congenital hemangioma, and caféau-lait spots. [2][3][4] To our knowledge, our case is the first reported case of Poland syndrome associated with multiple CMN.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…1 In addition to these known associations, a literature review revealed a few isolated cases of Poland syndrome with various congenital dermatologic findings, including recessive X-linked ichthyosis, congenital hemangioma, and caféau-lait spots. [2][3][4] To our knowledge, our case is the first reported case of Poland syndrome associated with multiple CMN.…”
mentioning
confidence: 62%
“…In this variant, commonly referred to as pityriasis circinata et marginata of Vidal or limb-girdle PR, the eruption generally appears in the axillae, the groin, or both, with the trunk and extremities usually spared. 4,5 A simple classification for atypical pityriasis rosea has been proposed by Chuh and Zawar (Box). 6 In our patient, the eruption fulfills all 3 essential clinical features (discrete annular lesions, scaling, and peripheral collarette scaling with central clearance on at least 2 lesions), all 3 optional clinical features (relative truncal distribution, orientation along skin cleavage lines, and herald patch), and none of the exclusional clinical features.…”
Section: Figure 2 Lesional Biopsy Specimen Obtained From the Left Thighmentioning
confidence: 99%
“…It often leaves a hyper-or hypo-pigmented macule [2,3]. The entire course of an eruption can take several years and, very often, lesions may be present in all stages of development [4]. Pityriasis lichenoides chronica usually occurs on the trunk and proximal parts of the extremities, but acral and segmental distributions have also been described, the lesions being usually asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of isomorphic lesions at the site of an injury in lichen planus, warts, molluscum contagiosum (Fig. 13), psoriasis, or lichen nitidus along a site of injury [23][24][25][26][27].…”
Section: Koebner Signmentioning
confidence: 99%